PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 01 TAMAN KOTA MADIUN - Reni Setyowati Agustina; Sudarmiani; Ibadullah Malawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aims to describe the implementation of the Discovery Learning model assisted by audio visual media and to improve the learning motivation and learning outcomes of fourth grade students in the Natural and Social Sciences (IPAS) subject at SDN 01 Taman Kota Madiun. The research was motivated by low learning motivation and learning outcomes, where the pre cycle showed that only 28% of students were motivated and 13.8% achieved the minimum mastery criteria. The study used a mixed method approach conducted in two cycles, each consisting of planning, acting, observing, and reflecting. The subjects were 29 fourth grade students. Data were collected through tests, questionnaires, observation, interviews, and documentation, then analyzed using quantitative descriptive statistics and the qualitative model of Miles and Huberman. The results showed that the average motivation score increased from 66.5 in the pre cycle to 74.3 in cycle I and 83.8 in cycle II, with the percentage of motivated students rising from 28% to 69% and reaching 100% in cycle II. Learning outcomes also improved, with the class average increasing from 64.9 in the pre cycle to 73.4 in cycle I and 82.4 in cycle II, and mastery rising from 13.8% to 69% and reaching 100% in cycle II. These findings confirm that the Discovery Learning model assisted by audio visual media effectively improves the learning motivation and learning outcomes of fourth grade students in IPAS.